2021
DOI: 10.1038/s41598-021-85599-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of provenance origin on the early performance of two sclerophyllous Mediterranean species established in burned drylands

Abstract: Forest restoration have had limited success due to intense and prolonged droughts in Mediterranean-type ecosystems. In this context, knowledge of growth and physiology in seedlings of different provenances can be useful in the selection of appropriate seed sources for restoration. In this study we investigated variations in survival, growth, and leaf-level physiology of five provenances of Quillaja saponaria Mol. and five provenances of Cryptocarya alba Mol. originated from coastal and Pre Andean sites exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Some studies comparing provenances in common garden experiments have shown better performance for local provenance origin than others more distant to the study site 23 , 34 , 41 , 42 , which is attributed to local adaptations (adaptative genetic changes) to specific edaphoclimatic conditions. However, other studies have shown a good performance of provenances out of their geographic origin, which are signs of maladaptive or non-adaptive genetic changes due to genetic drift or stresses induced by soil resource limitations 23 , 43 .…”
Section: Discussionmentioning
confidence: 90%
“…Some studies comparing provenances in common garden experiments have shown better performance for local provenance origin than others more distant to the study site 23 , 34 , 41 , 42 , which is attributed to local adaptations (adaptative genetic changes) to specific edaphoclimatic conditions. However, other studies have shown a good performance of provenances out of their geographic origin, which are signs of maladaptive or non-adaptive genetic changes due to genetic drift or stresses induced by soil resource limitations 23 , 43 .…”
Section: Discussionmentioning
confidence: 90%
“…Variability in germination among populations was reported in other forest species and shrubs [ 58 , 59 , 60 , 61 ] and is attributed to genetic differences and climatic and geographic effects [ 62 ]. The Mediterranean-type climate area of central Chile has a diversity of climatic conditions due to its geography and latitudinal variation in germination capacity and early performance was observed in species of the Nothofagus genus [ 61 , 63 , 64 ] and sclerophyllous species including C. alba [ 37 , 65 , 66 ]. In our study, the success of seed germination and survival of C. alba was significantly determined by the seed source, where only the local seed source CA showed some survival at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…At the nursery level, C . alba showed high phenotypic variability in the responses to water restriction [ 36 ]; however, at the landscape level, the successful establishment of the species is limited due to water scarcity [ 37 ]. In this context, there is a need for better information on how factors such as seed source and forest cover influence the recruitment of C .…”
Section: Introductionmentioning
confidence: 99%